Significados e atmosferas: a água como elemento arquitectónico - Ana Martins Francisco (2019)
This dissertation seeks to strengthen the relationship between the natural and the artificial, exploring ways of interpreting water as an architectural element. Its development is based on the problems raised by a competition of ideas, which is based on the discussion about the need for spaces that promote concentration, artistic inspiration and meditation, and that are refuges from the constant rhythm of urban life. In this sense, water emerges as a key theme of drawing which, by identifying its characteristics and exploring its multisensory dimension, is the mediating element of the interior/exterior relationship, and promotes the spatial and tectonic investigation of these atmospheres of relaxation, introspection and creativity.